AMBIGUITIES IN CHIRAL-SYMMETRY BREAKING USING THE EFFECTIVE POTENTIAL APPROACH - Montero, J. C.; PLEITEZ, V (Springer, 1991)
Using a form of the effective potential for composite operators with a variational approach we show that it is possible to get different directions of the chiral phase transition in QCD. Which one occurs depends on the way the Schwinger-Dyson equation for the fermion self-energy is used in the 2-loop term of the effective potential. We must choose the 2-loop term which agrees with phenomenology in each form of the effective potential.